2018
DOI: 10.1002/slct.201801996
|View full text |Cite
|
Sign up to set email alerts
|

α‐Csp3‐H Methylenation of Diketones to Synthesize Methylene‐Bridged Bis‐1,3‐Dicarbonyl Compounds and Polysubstituted Pyridines Using the DMSO/Selectfluor System

Abstract: A direct α‐Csp3‐H methylenation of 1,3‐diketones to afford methylene‐bridged bis‐1,3‐dicarbonyl derivatives using dimethyl sulfoxide (DMSO) as a one‐carbon source was achieved in moderate to high yields in the presence of Selectfluor. The 1,3‐diketones can also be efficiently converted into Hantzsch‐type pyridines via one‐pot three‐component annulation reaction in the presence of DMSO and ammonium salt. The procedure avoids the use of transition metal catalysts and the reaction is efficient and operationally c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Based on the aforementioned experimental results, and literature reports,, two plausible reaction mechanisms have been proposed to explain pyridine formation (Scheme ). Initially homo‐condensation of 1 at 120 °C yields a chalcone analogue A , which can react with ammonium acetate to give imine intermediate B.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the aforementioned experimental results, and literature reports,, two plausible reaction mechanisms have been proposed to explain pyridine formation (Scheme ). Initially homo‐condensation of 1 at 120 °C yields a chalcone analogue A , which can react with ammonium acetate to give imine intermediate B.…”
Section: Resultsmentioning
confidence: 99%
“…[27] Meanwhile, they also found that using this Selectfluor/DMSO system, the direct C(sp 3 )-H methylenation of 1,3-diketones could be achieved (Scheme 14b). [28] Very recently, the same group reported a novel and efficent strategy for the construction of 3-acylquinoline by using acetophenone, anthranil and DMSO as the strating materials through a Selectuor mediated three-component reaction (Scheme 14c). [29] It was noteworthy to mention that DMSO served as both a carbon and solvent source.…”
Section: The Application Of Selectfluor As a Fluorine Cation Initiator 31 Selectfluor As A Fluorinated Intermediate Initiatormentioning
confidence: 99%
“…56 The same group also reported the reaction anthranil is an isoxazole derivative which has been used for synthesis of a couple of heterocycles by cleavage of N-O bond. [57][58][59][60][61] Inspired by these excellent pioneering work, especially Tiwari's report that quinolines can be transformed from the reaction of in situ generated a,b- unsaturated ketones from acetophenones via one-carbon homologation by DMSO followed by the aza-Michael addition of anthranils and subsequent annulation, 62 we were encouraged to use Selectuor [63][64][65][66][67][68] as an alternative oxidant for the synthetic approach to 3-acylquinolines from commercially available acetophenones and anthranil. In this case, DMSO was applied as both carbon source and reaction medium.…”
Section: Introductionmentioning
confidence: 99%